Contamination of silicon by iron at temperatures below 800 degrees C - Murphy, J; Falster, R (2011)
Iron-related defects are deleterious in silicon-based integrated circuits and photovoltaics, ruining devices and acting as strong recombination centres. Unless great care is taken, iron contamination will result from high temperature processing and so it is essential to understand the degree to which this can occur. Iron solubility data above ~800 °C have been summarised by Istratov et al. (Appl. Phys. A 69, 13 (1999)), but many processes are performed at lower temperatures for which solubility data are scarce. We have studied iron contamination below ~800 °C. Iron concentrations in intentionally contaminated air-annealed Czochralski silicon samples were determined from the change in minority carrier lifetime due to photodissociation of FeB pairs measured by quasi-steady-state photoconductance. In the ~600 to 800 °C temperature range the iron concentration was found to vary according to. It is therefore the case that significantly more iron can dissolve in silicon at these temperatures than extrapolation of higher temperature data suggests, with the enhancement being by a factor of >20 at 600 °C. © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.